The Continued Saga of the CISG in the Nordic Countries: Reservations and Transformation Reconsidered - Thomas Neumann (Nordic Journal of Commercial Law, 2013)
Recently, there have been significant legislative changes in the Nordic rules concerning formation of contracts. Some of these changes have already taken effect while others will have effect in the near future. The present article provides an overview of the current status and challenges regarding the Nordic legislative changes. The changes are related primarily to the processes of withdrawing reservations made according to article 92 of the UN Convention on Contracts for International Sales of Goods (hereinafter CISG or the Convention).1 Before turning to the details it is beneficial first to introduce some salient parts of the Convention history in a Nordic perspective and to define more precisely, which countries are considered to be Nordic. The CISG is currently in force in 78 states.2 Its purpose is to create a uniform set of rules regarding formation and performance of contracts concerning trade in goods. By providing a textually uniform framework for businesses and by demanding its uniform application, the Convention is supposed to remove barriers to trade that exist in the form of differences between domestic rules.3 By having one and the same convention for the formation of contracts and contract performance it becomes easier for parties engaged in international trade of goods to predict their legal status, since the rules ideally are the same. Consequently, transaction costs are lowered and in the end, peace among nations is fostered. This of course presumes that both the Convention text and its application are uniform.4 Obviously, the trading parties are robbed of the possibility to predict their legal status, if the courts of the CISG contracting states do not apply the rules in a uniform manner. The same is true, if the Convention text that is being applied is not the same across countries. Differences in the Convention text or in its application lead to forum shopping and increase in transaction costs, which it was the intention to remove in the first place. Uniformity faces its adversaries at the textual level in two ways. Firstly, because the Convention exists in six equally authentic language versions which have discrepancies among themselves. Secondly, the application of the Convention text as a whole is undermined, when contracting states make reservations against the application of parts of the Convention. Though reservations may be seen as the necessary tool to provide the flexibility needed to convince states to actually adopt instruments like the CISG, they have the consequence that the provisions of the CISG are allowed to be applied differently (if applied at all) from state to state, and thus a reservation is a threat to uniformity at both the textual level and consequently also at the application level.5 Fortunately, a number of states are in the process of revoking their reservations. The latest notification of withdrawal was received by UNCITRAL in January 2013 and was made by China in regard to its original reservation against the freedom of form rule in the Convention.6 Other Soviet-influenced states like Latvia and Estonia have also withdrawn their reservations against the freedom of form made according to CISG article 12 and article 96.7 For the sake of uniformity such withdrawals are welcomed.